2007
DOI: 10.1523/jneurosci.0388-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

How Do Primates Anticipate Uncertain Future Events?

Abstract: The timing of an upcoming event depends on two factors: its temporal position, proximal or distal with respect to the present moment, and the unavoidable stochastic variability around this temporal position. We searched for a general mechanism that could describe how these two factors influence the anticipation of an upcoming event in an oculomotor task. Monkeys were trained to pursue a moving target with their eyes. During a delay period inserted before target motion onset, anticipatory pursuit responses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…This relationship accounted for timing changes both within and across ranges. History effects in the timing of eye movements have been observed previously (Heinen et al, 2005), and a reliance on previous stimulus probabilities in the control of anticipatory smooth pursuit initiation has been reported in monkeys (de Hemptinne et al, 2007). However, to our knowledge, there has been no previous demonstration of the quantitative association with past timing stimuli that we have demonstrated, the effect of which is to allow a running average of anticipatory timing to be estimated.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This relationship accounted for timing changes both within and across ranges. History effects in the timing of eye movements have been observed previously (Heinen et al, 2005), and a reliance on previous stimulus probabilities in the control of anticipatory smooth pursuit initiation has been reported in monkeys (de Hemptinne et al, 2007). However, to our knowledge, there has been no previous demonstration of the quantitative association with past timing stimuli that we have demonstrated, the effect of which is to allow a running average of anticipatory timing to be estimated.…”
Section: Discussionmentioning
confidence: 49%
“…This would not be surprising. Previously, when examining anticipatory responses to the onset of discrete pursuit stimuli, de Hemptinne et al (2007) showed that variability in cue timing is reflected in variability in response timing. Similar effects have been reported for saccades (Joiner and Shelhamer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the latency distribution of anticipatory pursuits is bimodal (Fig. 5A2,B2) (see also de Hemptinne et al, 2006de Hemptinne et al, , 2007. Figure 9 shows that the cumulative latency distribution of anticipatory pursuit movements shows two abrupt increases (onset indicated by vertical dashed lines; see also aЈ and bЈ).…”
Section: Modulation Of Neuronal Activity Related To Anticipatory Pursuitmentioning
confidence: 89%
“…Anticipatory smooth pursuit is a slow movement of the eyes occurring before the appearance of an expected moving target. It has been shown repeatedly that primates can generate anticipatory smooth pursuit in the absence of visual stimulation provided there is a strong expectation about the characteristics of upcoming target motion (Kowler andSteinman, 1979a,b, 1981;Kowler et al, 1984;Kowler, 1989;Barnes and Asselman, 1991;Barnes et al, 2002;Heinen et al, 2005;Badler and Heinen, 2006;de Hemptinne et al, 2007). The influence of expectation in the spatial domain is often studied by providing information using color cues that allow subjects to orient attention to the upcoming spatial position of a target (Posner, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Only saccades that occurred after the onset of launcher target motion were recorded. Pursuit onset was also detected using a previous algorithm (de Hemptinne et al, 2007). Filtered velocity was required to exceed a threshold of 2°/s for at least 100 ms to be classified as pursuit.…”
Section: Methodsmentioning
confidence: 99%